Phylogenetic dimension of tree communities reveals high conservation value of disturbed tropical rain forests. Issue 6 (26th February 2018) - Santo‐Silva, Edgar E.; Santos, Bráulio A.; Arroyo‐Rodríguez, Víctor; Melo, Felipe P. L.; Faria, Deborah; Cazetta, Eliana; Mariano‐Neto, Eduardo; Hernández‐Ruedas, Manuel A.; Tabarelli, Marcelo
Abstract: Aim: The conversion of old‐growth tropical forests into human‐modified landscapes threatens biodiversity worldwide, but its impact on the phylogenetic dimension of remaining communities is still poorly known. Negative and neutral responses of tree phylogenetic diversity to land use change have been reported at local and landscape scales. Here, we hypothesized that such variable responses to disturbance depend on the regional context, being stronger in more degraded rain forest regions with a longer history of land use. Location: Six regions in Mexico and Brazil. Methods: We used a large vegetation database (6, 923 trees from 686 species) recorded in 98 50‐ha landscapes distributed across two Brazilian and four Mexican regions, which exhibit different degrees of disturbance. In each region, we assessed whether phylogenetic alpha and beta diversities were related to landscape‐scale forest loss, the percentage of shade‐intolerant species (a proxy of local disturbance) and/or the relatedness of decreasing (losers) and increasing (winners) taxa. Results: Contrary to our expectations, the percentage of forest cover and shade‐intolerant species were weakly related to phylogenetic alpha and beta diversities in all but one region. Loser species were generally as dispersed across the phylogeny as winner species, allowing more degraded, deforested and species‐poorer forests to sustain relatively high levels of evolutionary (phylogenetic) diversity. Main conclusion: Our findings support previous evidence indicating that traits related to high susceptibility to forest disturbances are convergent or have low phylogenetic signal. More importantly, they reveal that the evolutionary value of disturbed forests is (at least in a phylogenetic sense) much greater than previously thought.